2006
DOI: 10.1007/s10750-006-0359-x
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of substrate morphology and surface area on phytofauna

Abstract: The independent effects and interactions between substrate morphology and substrate surface area on invertebrate density or biomass colonizing artificial plant beds were assessed in a clear-water and a turbid playa lake in Castro County, Texas, USA. Total invertebrate density and biomass were consistently greater on filiform substrates than on laminar substrates with equivalent substrate surface areas. The relationship among treatments (substrates with different morphologies and surface areas) and response (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…However, that study estimated macrophyte complexity et al 2010). However, several authors have reported an effect of complexity per se on invertebrates (Taniguchi et al 2003;Hauser et al 2006;Becerra-Mun ˜oz and Schramm 2007). As POM and Chl-a are usually positively related to complexity (Warfe and Barmuta 2006;Lucena-Moya and Duggan 2011), it is often difficult to disentangle their effects and to conclude whether food availability is the main factor driving invertebrate colonization of macrophytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study estimated macrophyte complexity et al 2010). However, several authors have reported an effect of complexity per se on invertebrates (Taniguchi et al 2003;Hauser et al 2006;Becerra-Mun ˜oz and Schramm 2007). As POM and Chl-a are usually positively related to complexity (Warfe and Barmuta 2006;Lucena-Moya and Duggan 2011), it is often difficult to disentangle their effects and to conclude whether food availability is the main factor driving invertebrate colonization of macrophytes.…”
Section: Discussionmentioning
confidence: 99%
“…To date a number of field and laboratory studies have focused on the relationships between plant morphology (substrate surface, habitat complexity) and associated invertebrates (Lalonde and Dowing 1991;Taniguchi et al 2003;Tessier et al 2004;Becerra-Munoz and Schramm 2007;Hansen et al 2011). Only a few considered the structure and biomass of periphytic algae as a factor potentially determining the selection of macrophyte species by invertebrates (Dvorak 1996;Cattaneo et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Substrate composition and surface heterogeneity of the introduced structures are important factors for settling organisms (Mullineaux and Garland 1993;Walters and Wethey 1996;Becerra-Muñoz and Schramm Jr 2007). Settling larvae of various species have diVerent preferences for Xow speeds of the boundary layer and chemical cues from resident species may also play a role (Mullineaux and Butman 1991;Koehl 2007).…”
Section: Introductionmentioning
confidence: 99%